Anisotropy and amplification of terahertz electromagnetic response enabled by direct electric current in graphene - Моисеенко , Илья Михайлович; Fateev, Denis Васильевич; Popov, Vyacheslav Valentinovich (Известия высших учебных заведений: Прикладная нелинейная динамика)
The purpose of this study is to investigate the polarization conversion and amplification of electromagnetic terahertz (THz) wave incident normally upon graphene monolayer with direct electric current flowing at arbitrary angle to the elecric vector of incident wave. Methods. The expressions for the elements of the dynamic conductivity tensor of graphene were obtained in hydrodynamic approximation. The electromagnetic response is calculated by solving the Maxwell equations with standard boundary conditions for lateral components of the electric and magnetic fields. Results. It is shown that the dynamic conductivity of graphene depends on value and direction of the electron drift velocity even in the absence of the spatial dispersion. This results in the polarization conversion of electromagnetic radiation at THz frequencies. The real parts of elements of graphene dynamic conductivity tensor can become negative which leads to the amplification of THz oscillations. Conclusion. The polarization conversion and amplification of electromagnetic THz wave incident upon graphene with direct electric current is demonstrated. Polarization conversion efficiency can be as high as 97 percent.